Influence of Convection Heat Transfer on Circular Tube Structure of Polar Marine Engineering Equipment - CAO Taichun, WU Gang, KONG Xiangyi, YU Dongwei, WU Lin, ZHANG Dayong (Shanghai Jiaotong Daxue xuebao, 2023)
Electric heat tracing is often used for cold protection in polar ocean engineering equipment. Heat balance is the key problem of convective heat transfer. In this paper, the circular tube structure is taken as the research object. Numerical simulations using Fluent and model experiment are conducted to analyze the change of the convective heat transfer coefficient of the circular tube component under the polar environment with a wind speed range of 0—40 m/s and a temperature range of -40—0 ℃. Based on the numerical simulation data, the prediction model of the convective heat transfer coefficient of the electric heating tube is obtained. The results show that the convective heat transfer coefficient increases with the increase of wind speed and the decrease of temperature. When the temperature is below -30 ℃, or when the wind speed is greater than 25 m/s and the temperature is lower than -20 ℃, the influence of temperature on the convective heat transfer coefficient increases. The rationality of the model is verified by experimental test.